Future of Anesthesia: Is Artificial Intelligence Implementation Near? - Brusich, Katarina Tomulić; Šestan, Mia; Seršić, Lara Valenčić (International Journal of Innovative Research in Medical Science, 2025)
The implementation of artificial intelligence (AI) becomes increasingly prevalent due to advancements in technology and has the potential to significantly enhance the future of anesthesia and critical care. This article concisely summarizes contemporary AI technology utilized in anesthesia and in the intensive care unit (ICU). The current data indicates that the incorporation of AI could have a substantial impact on areas such as chronic disease management and anesthesia education methods, necessitating the development of specialized studies to investigate these applications. Nevertheless, current AI implementations predominantly function as decision-support tools rather than replacements for clinical judgment, despite the immense potential of AI to enhance the capabilities of anesthesiologists. Additionally, the limitations and ethical considerations of AI implementation in this domain are discussed.